Shalat Perspektif Kaum Sufi - Ihsan Sobari; Hasan Mud'is; Muhtar Gojali (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2019)
One way for a servant to establish good relations with God is to pray. prayer is a form of worship of a servant to his God who can prevent it from vile and evil deeds. If humans are able to pray well, then the potential to commit crimes will be closed. However, some of the people who perform prayers but the immoral acts are also cariied out is not used as a method of self transformation in order to be able to prevent themselves from vile and mockery.This background raises some formulation of the problem, namely how to pray in the sufi view, in this case Imam Al-Ghazali and Ibnu Qayyim Al-Jauzi who is a Sufi figure popular among students of sufism and spiritual walkers. With the comparative study of the sufi figures, it will respresent other thoughts about prayer. Then the formulation of the next problem ia about how similarities are also different views about prayer. The purpose of this study was to find out and understand the views of the sufis, in this case Imam Al-Ghazali and Ibnu Qayyim Al-Jauzi, about how to pray in their view and to know the differences in their similarity of views about prayer.Al-Ghazali argues that prayer is actually dhikr, reading, munajat, and dialogue. but, it will not happen without the presence of the heart. Ibnu Qayyim Al-Jauziyah defines prayer by exposing the heart to Allah and presenting the total heart to him. If the heart is not facing God and is busy with others and lulled by the whisper of his lust, he is like a guest visiting the royal palace to express the reason for all his mistakes and forgetfulness, expecting a cloud of kindness, compassion and mercy, and proposing a number of things can strengthen his heart to be more loyal to serve. Prayers and worship are actually prayer and heart worship. If the heart is negligent and solemn or not concentrating in prayer, the physical prayer will fall apart. If this happens, the physical peace that is expected to come through physical prayer will not be achived. physical prayer can only be done with a solemn heart.